Camera-based Automatic System for Tool Measurements and Recognition. (2016) - Mikołajczyk, Tadeusz; Kłodowski, Adam; Mrozinski, Adam
Abstract: In the last decades video capturing technology has become inexpensive, good quality and thus broadly used. Video cameras are currently one of the inexpensive sensors giving large amount of meaningful data. This paper focuses on the usage of an automated video-based system for turning tools base plane wear assessment. Paper presents algorithms and image processing routines required for successful implementation of such a system. Presented system consists of a USB camera with VGA resolution combined with software tools required to perform tool wear analysis. Picture acquisition and analysis software was developed using Visual Basic. Analyses can be conducted on selected regions of the image. Software is capable of image segmentation aimed at automated tool identification in the image as well as assessing geometrical parameters of the tools' cutting edge in the base plane. Program uses knowledge base for tools' wear identification. The presented method has been verified to show validity of the concept. The concept was found to be of practical importance and also convenient as a tool for teaching.